Diplomats - Philadelphia Record (1941-1946)
Depicts the Japanese Consulate in the Land Title Building and the Spanish Consulate at 17th and Locust, both in Philadelphia. Pickets are shown in front of the Spanish consulate supporting the coffee resolution against Franco.
These subject entries for the Philadelphia Record newspaper's photo morgue are primarily for Places (buildings, parks, streets, etc.), Things (Bicycles, Bison, Blind Persons [just sampling the B's]), Events (Democratic National Convention 1936, Flourtown Fair, Harvest Week) and Social Constructs (Home Economics, City Planning, Eating & Drinking, etc.). Each of these subjects became a MARC record which included a call number. In the case of these records, the call numbers are the actual folder numbers for the materials referenced. Therefore, these subject headings are really also an index for this section of the Philadelphia Record newspaper's photograph morgue. [The name section of the Philadelphia Record photo morgue represents individuals, A-Z, and
Part of the Philadelphia Record Photograph Morgue Collection; for general information, see collection record.
Gift of the Philadelphia Record
Keywords: International relations; Diplomats -- Japanese -- Pennsylvania -- Philadelphia; Diplomats -- Spanish -- Pennsylvania -- Philadelphia; Pickets -- Pennsylvania -- Philadelphia